PRICING STRATEGY FOR HOTELS IN MANADO: A QUALITATIVE STUDY - Tambuwun, Rigita Ratnasari; Worang, Frederik G.; Pandowo, Merinda H. C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: The aim of this research is to find out the pricing strategy that is utilized by hotels in Manado and what are the factors affecting pricing decision. This research using qualitative approach and the data was gathered by in-depth interview with seven informants, in this case the sales and marketing manager and accounting manager of the hotels. The result shows that each hotel using two pricing strategies and there are three hotels using similar strategy and the others using different pricing strategy than the other hotel. This research found the most preferable pricing strategy used by hotels in Manado are Hi-Lo season strategy, Demand-based pricing, Competition-based pricing, cost-based pricing, price per segment, and customer willingness to pay. The research recommends the hotels to keep updating their strategy because most of the hotels in determine the price depends on the market demand and seasonality. In this case, the hotels have to do more in promoting their hotels especially during low season. For additional, the government also have to develop the tourism in Manado so that many tourists arrive which results in the demand for hotel room increase.Â Â Keywords: pricing strategy, price determinants, star hotels in manado, qualitative study